EVALUATION OF LEARNING PHYSICAL EDUCATION IN THE COVID-19 PANDEMIC - Ade Argi; Ramdan Pelana; Yasep Setiakarnawijaya (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
The purpose of this study was to determine the level of effectiveness of physical education virtual learning during the COVID-19 pandemic first grade students of 6 junior high school Bogor. The research method used is to use a descriptive qualitative research method, namely a survey using Google form media which is carried out in each house. The population in this study were students of 6 junior high school Bogor mounting to 306 students and using a sample of 34 students in the same class. This study used an instrument in the form of a questionnaire with variables. This research includes three aspects of affective, cognitive and psychomotor. Affective here uses a research instrument in the form of a questionnaire to obtain research data with a total of 18 questions with answer options Strongly, Agree, Disagree, Strongly Disagree Based on the results of research analysis and discussion, it can be concluded that the level of physical education learning during the COVID-19 pandemic can be broken down as follows the affective category average is 33.56, the cognitive average is 89.56 and the psychomotor is 78.67. From the three data, it was found that the average level of learning effectiveness was 67.27 with the category less